PENGGUNAAN MODUL PADA PEMBELAJARAN TEMATIK DI SDN 1 JIMBUNG KLATEN - Muhroji Muhroji; Husna Yusrina (Profesi Pendidikan Dasar, 2018)
Abstract: This study aims to determine the effect of the use of modules in thematic learning on the learning outcomes in SD Negeri 1 Jimbung. This is quantitative research. Data collection techniques use tests, both pretest and posttest. Data analysis using paired test of t-test and gain test. The result of paired sample t-test to the value of pretest and posttest obtained sig value equal to 0.000 which is smaller than 5% significance level, that is 0.000 0.05 so there is difference, that result of posttest value higher than at result of pretest value. The difference in student learning outcomes can be seen from the gain test which has an average of 0.407, including the category of "moderate increase". So it can be concluded that the use of the module affects the improvement of learning outcomes of thematic learning of students in grade IV in SD Negeri 1 Jimbung.